Rumah Adat Joglo Pencu Kudus: Sejarah Makna-makna Keislaman dalam Arsitektur Rumah Adat Kudus Joglo Pencu - Jauharatul Kamila Afliha (IIQ An Nur Yogyakarta, 2022)
This study emphasizes two problems: (1) What is the history of the traditional house of Kudus Joglo Pencu and its development; (2) What are the meanings and values in the Joglo Pencu traditional house. This study finds the Islamic meanings, decorations, and architectural arts found in the Kudus traditional house. The approach used in this research is architectural-anthropology. This theory explains the relationship between function, form and meaning in four stages, namely heuristics, interpretation, interpretation, and historiography. The results of this study indicate that the traditional house of Kudus Joglo Pencu existed in 1500 AD with original teak wood through the roles of Sunan Kudus and Kiai Telingsing. The form of this Kudus traditional house architecture is the development of Javanese traditional houses which are influenced by Chinese, European, and Persian cultures. The traditional house of Kudus Joglo Pencu has Islamic values such as on the top of the roof of the king's roof with plant motifs that humans live must take refuge in Allah.